Internal Controls to Curb Corruption in the Police Department: Challenges and Way Forward - Raza, Syed Ali (Journal of Pakistan Administration, 2023)
In the developing countries like Pakistan the expectations from the systems are democratic but the basic structures are colonial. Historically speaking, the Police Act of 1861 did not provide much scope to police accountability which was later altered and amended in Article (8) of The Police Order 2002 (PO) that has put in place a system of police accountability based on public participation and community input. Article 155 of PO 2002 explains the penalty for certain types of misconduct. According to the Transparency International Corruption Perception Index 2021 (2022), Pakistan is at 140th number out of 180 countries. Keeping in view these statistics the study of the reasons of corruption and their remedies in police become imperative. In Pakistan where religious intolerance, sectarian, ethnic, and gender-based violence is on the rise and on the other hand there is stagnant economic growth coupled with high rates of inflation, unemployment, poverty, and income inequality, under such situations if the law enforcement department of the country itself faces the challenges like corruption and lack of integrity, then rule of law and writ of the state are the foremost casualties. Political, social, economic, and cultural factors are the main contributory factors in increasing corruption. Corruption in police is a reality but perception makes it the worst. Internal controls have been devised in the system however optimal results are not achieved. A well-coordinated reform regime is required to make Police corruption free.